Coverage of Native Plants Is Key Factor Influencing the Invasibility of Freshwater Ecosystems by Exotic Plants in China - Yu, Haihao; Wang, Ligong; Liu, Chunhua; Fan, Shufeng (Frontiers in Plant Science, 2018)
Understanding the biotic and abiotic factors that influence the susceptibility of a community to invasion is beneficial to the prediction and management of invasive species and the conservation of native biodiversity. However, relationships between factors and invasibility of community have not been fully confirmed, and which factors are most associated with susceptibility of community to invasion were rarely studied. In this study, we investigated the species richness patterns in aquatic exotic and native plants and the relationships of exotic species richness with habitat and water environment factors in 262 aquatic plant communities in China. A total of 11 exotic plant species were recorded in our field survey. We found that there is neither a negative nor a positive relationship between aquatic exotic and native plant species richness. Aquatic exotic plant richness is negatively correlated with the relative coverage and biomass of native plants but positively correlated with total nitrogen (TN), total phosphorus (TP) and chemical oxygen demand (COD) concentrations in the water. Native plant richness, native relative coverage, and native biomass were positively related to each other, while TP, TN, and COD were also positively related to each other. Native plant richness, native relative coverage and native biomass were each negatively correlated with all TP, TN and COD. In addition, biotic predictors rather than abiotic predictors accounted for more of the variation in exotic plant richness. Our results suggested that improving vegetation coverage and biodiversity of native plant is the most effective approach to prevent alien plant invasions and minimize their impacts in freshwater ecosystems.